Leaf morphological variations and heterophylly in ficus deltoidea Jack (Moraceae) - Nashriyah Mat,; Nurrul Akmar Rosni,; Nor Zaimah Ab Rashid,; Norhaslinda Haron,; Zanariah Mohd Nor,; Nur Fatihah Hasan Nudin,; Abd Ghani Yunus,; Abdul Manaf Ali, (Universiti Kebangsaan Malaysia, 2012)
Six varieties of Ficus deltoidea Jack (Moraceae) showed leaf morphological variations through quantitative measurement on different plant parts. There were significant differences among six varieties studied by plant parts. The varieties studied include var. deltoidea Corner, var. angustifolia (Miq.) Corner, var. trengganuensis Corner, var. bilobata Corner, var. intermedia Corner, and var. kunstleri (King) Corner. The upper, middle and lower plant parts showed morphological variations in terms of leaf length, leaf width, leaf area and petiole length. Qualitative parameters also showed trends in morphological variations in terms of leaf shape, leaf base, leaf apex and leaf attachment. However, some qualitative parameters were not the recommended parameters to differentiate among varieties. On the other hand, leaf heterophylly has occurred in F. deltoidea because foliage of the young plant was different from the mature plant. Leaf heterophylly was observed in leaf shape and leaf apex parameters, whereby leaves from the lower plant parts were different from the upper and middle parts. The heterophylly in leaf shape was detected in varieties angustifolia, bilobata, intermedia and trengganuensis, whilst six varieties of F. deltoidea showed leaf apex heterophylly.